The Effect of Farmers' Exchange Rates on Rice Prices in 2017-2019 - Pujiono Eddy; Sudarno; Nicholas Renaldo; Marice Br Hutahuruk; Muhammad Pringgo Prayetno (First Ciera Publisher, 2023)
This research aims to predict the price of rice in the mill according to quality (Rupiah/Kg) at a premium, medium and low levels in Indonesia. Then also to find out whether there is an effect of farmer exchange rates on the price of rice in mills at a premium level. The study used purposive sampling, namely samples in Indonesia. Data analysis using simple linear regression. The results showed that there was an effect of the farmer's exchange rate on the price of rice in the mill at the premium level of 69.16%, the farmer's exchange rate affected the price of the rice in the mill according to the quality (Rupiah/Kg) at the premium level. The recommendation that can be given is that the government can take steps to maintain the stability of farmers' currency exchange rates, especially in the face of global economic fluctuations. Appropriate fiscal and monetary policies can help reduce the risk of exchange rate volatility and have an impact on rice price stability at the mill. A robust monitoring system is needed to monitor exchange rate fluctuations and rice prices on a regular basis.